Chinese Annals in the Western Observatory - Shaugnessy, Edward (Library of Sinology, 2020)
Since the beginning of the twentieth century, hundreds of thousands of documents of all sorts have been unearthed in China, opening whole new fields of study and transforming our modern understanding of ancient China. While these discoveries have necessarily taken place in China, Western scholars have also contributed to the study of these documents throughout this entire period. This book provides a comprehensive survey of the contributions of these Western scholars to the field of Chinese paleography, and especially to study of oracle-bone inscriptions, bronze and stone inscriptions, and manuscripts written on bamboo and silk. Each of these topics is provided with a comprehensive narrative history of studies by Western scholars, as well as an exhaustive bibliography and biographies of important scholars in the field. It is also supplied with a list of Chinese translations of these studies, as well as a complete index of authors and their works. Whether the reader is interested in the history of ancient China, ancient Chinese paleographic documents, or just in the history of the study of China as it has developed in the West, this book provides one of the most complete accounts available to date.